The effect of muzzle blast wave on light screen in external ballistic measurement - Duan, Chenxi; Ni, Jinping; Tian, Hui; He, Biao; Li, Jing (Frontiers in Physics, 2025)
IntroductionIn measuring initial velocity, light screen detectors (LSD) are positioned closer to the muzzle. The light screen of the LSD can be affected by the muzzle blast wave (MBW), resulting in an inaccurate initial velocity.MethodsA method for analyzing the effect of the MBW as it passes through the light screen is proposed in this article. First, based on the ray tracing method the refraction equation is established. The equation is to explain the transmission of rays from the light screen within the MBW media. Second, the equation is solved numerically using the fourth-order Runge-Kutta method. Then, the dynamical process of the MBW passing through the light screen is analyzed using the discretization method. Finally, the radiation flux on the photosensitive surface at the LSD receiver is analyzed quantitatively. The radiation flux for the MBW passing through the light screen located at different distances from the muzzle is analyzed in simulations and experiments.ResultsThe mean absolute error between them and the theoretical calculation does not exceed 0.1.DiscussionThe results have been reasonably explained regarding the effect of the MBW as it passes through the light screen. This investigation not only helps the identification of the projectile signal in the light screen but also assists in identifying the MBW signal through independent measurements.